THE ROLE OF DIGITAL AND INNOVATIVE TECHNOLOGIES IN ENHANCING STUDENT ENGAGEMENT IN MODERN CLASSROOMS - Abdulhakimova Sarvinoz, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the role of digital and innovative technologies in enhancing student engagement in modern classrooms. It explores how interactive tools, online platforms, and multimedia resources contribute to more effective teaching and learning. The study highlights the impact of technology on fostering critical thinking, creativity, collaboration, and personalized learning among students. Emphasis is placed on practical strategies for integrating digital innovations into teaching practices to create dynamic and student-centered learning environments.